Tropical seagrass meadows modify seawater carbon chemistry: implications for coral reefs impacted by ocean acidification - Unsworth, R; Collier, C; Henderson, G; McKenzie, L (2012)
Highly productive tropical seagrasses often live adjacent to or among coral reefs and utilize large amounts of inorganic carbon. In this study, the effect of seagrass productivity on seawater carbonate chemistry and coral calcification was modelled on the basis of an analysis of published data. Published data (11 studies, 64 records) reveal that seagrass meadows in the Indo-Pacific have an 83% chance of being net autotrophic, resulting in an average net sink of 155gCm2yr1. The capacities for seagrass productivity were analysed using an empirical model to examine the effect on seawater carbonate chemistry. Our analyses indicate that increases in pH of up to 0.38 units, and Ωarag increases of 2.9 are possible in the presence of seagrass meadows (compared to their absence) with the precise values of these increases dependent on water residence time (tidal flushing) and water depth. In shallow water reef environments, Scleractinian coral calcification downstream of seagrass has the potential to be 18% greater than in an environment without seagrass. If this potential benefit to reef calcifiers is supported by further study it offers a potential tool in marine park management at a local scale. The applicability of this will depend upon local physical conditions as well as the spatial configuration of habitats, and the factors that influence their productivity. This novel study suggests that, in addition to their importance to fisheries, sediment stabilization and primary production, seagrass meadows may enhance coral reef resilience to future ocean acidification. © 2012 IOP Publishing Ltd.